COPING STRATEGY OF GIRL IN A POLYGAMOUS FAMILY - Muhimmatus Syarifah (UIN Sunan Kalijaga Yogyakarta, 2020)
A happy family is a dream for all people, both parents and children will surely want it. But if happiness is not intact in a family, then the family members will feel disappointed, even when the cause of the unharmony is something intense and constant will make them stressed. This study reveals about the life experiences of two girls who experience disharmony in the family because their father decided to remarry (polygamy) with a unilateral agreement. The depiction of stressful conditions and strategies in addressing them experienced by both girls is the main focus of this research. Being something of interest, though the experience of living in their family is not more beautiful and perfect than the other, but the two daughters are able to prove to the world that they are able to live a good life without wreak Negative behavior. They were able to continue the dream, one of which was to pursue education to a higher level. The type of method in this study is qualitative using a phenomenological approach. The data retrieval techniques are taken by conducting in-depth interviews with two female students who have the experience of living in a polygamous family. Both respondents applied a positive coping with, which is a coping with that focuses on emotional countermeasures such as positive reappraisal (giving positive meaning), Accepting Responsibility (emphasis on responsibility) as well as Self Controlling (able to control self).Keywords: Coping, daughter, polygamy